2002
DOI: 10.1007/s00330-001-1280-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of investigator experience in CT colonography

Abstract: The aim of this study was to determine the impact of the learning curve on the diagnostic performances of CT colonography. Two blinded teams, each having a radiologist and gastroenterologist, prospectively examined 50 patients using helical CT scan followed by colonoscopy. Intermediate data evaluation was performed after 24 data sets (group 1) and compared with data from 26 subsequent patients (group 2). Parameters evaluated included sensitivity, specificity, false-positive and false-negative findings, time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…This constant "drip feeding" of CT colonographic- endoscopic correlation is likely to be a more effective educational process than a one-off review of 50 consecutive cases. In a study by Gluecker and colleagues [9], two sets of readers analysed 50 cases but had access to endoscopic findings after first 24; there was no improvement in polyp sensitivity for the second 26 cases compared to the first 24. Alternatively, Pescatore and colleagues [10] found increased detection rates after 25 blinded CT colonographic studies for one individual radiologist, with diagnostic performance continuing to improve as experience approached 100 cases.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This constant "drip feeding" of CT colonographic- endoscopic correlation is likely to be a more effective educational process than a one-off review of 50 consecutive cases. In a study by Gluecker and colleagues [9], two sets of readers analysed 50 cases but had access to endoscopic findings after first 24; there was no improvement in polyp sensitivity for the second 26 cases compared to the first 24. Alternatively, Pescatore and colleagues [10] found increased detection rates after 25 blinded CT colonographic studies for one individual radiologist, with diagnostic performance continuing to improve as experience approached 100 cases.…”
Section: Discussionmentioning
confidence: 97%
“…McFarland and colleagues demonstrated that detection of large polyps ranged from 60 to 78%, even amongst experienced abdominal radiologists with equivalent colonographic training [11]. Furthermore, reader performance has been shown to continue to improve after just 25 cases [9,10]. At the present time, there is no consensus regarding what represents adequate reader training for CT colonography, probably because there is little evidence on which to base assumptions.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The use of 3D and MPR images in CT colonography requires dedicated software and familiarity with these image-manipulation techniques. It has been recommended that radiologists be trained in such techniques prior to interpreting CT colonography studies in a clinical setting [22]. In a busy department staffed by general radiologists, it may not be practical to devote the effort to including CT colonography in the routine work list.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there appears to be a ‘learning curve’ associated with learning how to read CT colonography. Some investigators have found that accuracy increased after reading 25 cases [68], while in another study, sensitivity improved after reading 50 cases and appeared ideal after interpreting 75 cases [69]. In a study with novice readers, specifically medical students and radiology technologists, after training using a teaching file of 50 cases followed by blind interpretation of 50 cases, these readers performed similarly to radiologists and improved in proportion to case volume up to 100 cases [64].…”
Section: Trainingmentioning
confidence: 99%